Aplicabilidade de novos biomarcadores em nefrite lúpica - Piraciaba, Tamires Teixeira [UNIFESP] (2019)
INTRODUCTION: Lupus Nephritis (LN) is one of the most common and serious manifestations of systemic lupus erythematosus (SLE) and affects about 60% of adults with the disease. Traditional markers such as sereum creatinine, hematuria, and proteinuria, and validated scores such as the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K), are used to follow these patients. New biomarkers are being studied as additional tools in clinical practice. OBJECTIVES: To assess serum levels of VEGF and suPAR and urinary levels of suPAR as markers of disease activity in individuals with LN. PATIENTS AND METHODS: Fifty-one patients aged 18 years or older, with a diagnosis of SLE were evaluated, based on the presence of at least four criteria of the American Association of Rheumatology and renal biopsy with LN. RESULTS: The majority of the patients were female (88.2%), white (51.0%) and with a mean age of 36.1 years. The majority belonged to classes IV (51.0%) and V (31.4%) with median disease duration of 2.5 years, ranging from 1 month to 32.0 years. In laboratory tests, 28 (54.9%) presented hematuria; proteinuria levels above 3.5 g /24h were observed in 17 (33.3%) patients, negative anti DNA and normal serum albumin were confirmed in 34 (66.7%) patients. The median SLEDAI-2K score was 11, ranging from 0 to 23. Proteinuria levels were not shown to be related to urinary suPAR, VEGF and serum suPAR. Patients with hematuria presented higher levels of urinary suPAR when compared to those without hematuria and there was an increasing correlation between SLEDAI-2K and urinary suPAR. CONCLUSIONS: In this population with LN, there was a predominance of women with class IV. Most had moderate disease activity according to SLEDA-2K. Urinary suPAR levels were found to correlate with the presence of hematuria and with elevated levels of the score. In this study there was no association of VEGF or serum suPAR with other markers.